Infection Dynamics of Clostridium perfringens Fingerprinting in Buffalo and Cattle of Punjab Province, Pakistan - Zafar Khan, Muhammad Umar; Khalid, Shumaila; Humza, Muhammad; Yang, Shunli; Alvi, Mughees Aizaz; Munir, Tahir; Ahmad, Waqar; Iqbal, Muhammad Zahid; Tahir, Muhammad Farooq; Liu, Yongsheng; Zhang, Jie (Frontiers in Veterinary Science, 2022)
Clostridium perfringens produces core virulence factors that are responsible for causing hemorrhagic abomasitis and enterotoxemia making food, animals, and humans susceptible to its infection. In this study, C. perfringens was isolated from necropsied intestinal content of buffalo and cattle belonging to four major bovine-producing regions in the Punjab Province of Pakistan for the purpose offind out the genetic variation. Out of total 160 bovine samples (n: 160), thirty-three (n: 33) isolates of C. perfringens were obtained from buffalo (Bubales bubalis) and cattle (Bos indicus) that were further subjected to biochemical tests; 16S rRNA based identification and toxinotyping was done using PCR (Polymerase Chain Reaction) and PFGE (Pulse Field Gel Electrophoresis) pulsotypesfor genetic diversity. Occurrence of C. perfringens was found to be maximum in zone-IV (Bhakkar and Dera Ghazi Khan) according to the heatmap. Correlation was found to be significant and positive among the toxinotypes (α-toxin, and ε-toxin). Response surface methodology (RSM) via central composite design (CCD) and Box-Behnken design (BBD) demonstrated substantial frequency of C. perfringens based toxinotypes in all sampling zones. PFGE distinguished all isolates into 26 different pulsotypes using SmaI subtyping. Co-clustering analysis based on PFGE further decoded a diversegenetic relationship among the collected isolates. This study could help us to advance toward disease array of C. perfringens and its probable transmission and control. This study demonstrates PFGE patterns from Pakistan, and typing of C. perfringens by PFGE helps illustrate and mitigate the incidence of running pulsotypes.